Moral, Trust and Happiness -Why Does Trust Improves Happiness? - Yagi, Tadashi (Journal of Organizational Psychology, 2017)
This paper explores the relationship between trust and happiness. It specifically looks at more moral investment behavior across five countries. To explore this topic, survey data from five countries analyzed. The results suggest that moral investment behavior differs among countries and societies depending on the trust level, and there possibly exists a vicious cycle in moral investment behavior. However, the return from moral investment might not be restricted to economic aspects. Trust within a society may affects the happiness of individual directly without passing through economic channel. Trust within community may enrich the life, improve the sense of security, relieve anxiety, or remedy the sense of loneliness.